The scar of visibility : medical performances and contemporary art - Kuppers, Petra (University of Minnesota Press, 2007)
In The Scar of Visibility, Petra Kuppers examines the use of medical imagery practices in contemporary art, as well as different arts of everyday life. Among the works she investigates are the controversial Body Worlds exhibition of plastinized corpses, films like David Cronenbergs Crash that fetishize body wounds, representations of the AIDS virus on CSI: Crime Scene Investigations, and the paintings of outsider artist Martin Ram?rez.